PENCIPTAAN HABITUS BARU PADA WARGA BINAAN PEMASYARAKATAN (WBP) DI LAPAS KELAS II B KARANGASEM - Utami, Ni Luh Srisaka; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study aims to describe and the phenomenon of habitus in class II B prison in Karangasem. This study uses a qualitative approach with descriptive and explanative types that aim to describe and summarize the habitus in Karangasem prisons. The theory used is the habitus theory of Pierre Felix Bourdieu. The results showed how different habits before and after entering prison can slowly influence mental structure through activities and discipline that are applied in prison. Habitus is influenced by domain and capital. The domain in this research is class II B Karangasem prison, while prison capital is the regulations and capital owned by officers, namely social capital, symbolic capital, and cultural capital. Habitus produces practices that are also influenced by doxa, heterodoxa, and orthodoxa, namely sanctions and attempts to destroy discourse through violations committed by WBP. Key words: Prisoners, habitus, Lapas class II B Karangasem